2006
DOI: 10.1002/mrd.20590
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of the accessory sex glands associated with the oocyte‐penetrating capacity of cauda epididymal sperm from holstein bulls of documented fertility

Abstract: We previously reported that accessory sex gland fluid (AGF) from high fertility (HF) bulls influenced the oocyte-penetrating capacity of cauda epididymal sperm from low fertility (LF) bulls, based on in vitro fertilization (IVF) assays. The present study determined if AGF proteins were associated with these effects. Nineteen IVF assays with 12 bulls were grouped as follows. Group I (n = 8): assays where sperm from LF bulls exposed to AGF from HF bulls had greater oocyte penetration than exposed to homologous A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
3
38
0
1
Order By: Relevance
“…Thus, the presence of this protein in ejaculated sperm could indicate its importance on the reproductive tract. Indeed, the presence of nucleobindin 2 in the AGF (Moura et al, 2007a) and CEF (Moura et al, 2007b) of the bull was already reported. In addition, there is practically no information about the role of nucleobindin in the male reproductive tract, and herein this work brings new information about this protein's interaction with the midpiece of ejaculated sperm, suggesting that the multifunctional nucleobindin may in fact influence sperm metabolism.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Thus, the presence of this protein in ejaculated sperm could indicate its importance on the reproductive tract. Indeed, the presence of nucleobindin 2 in the AGF (Moura et al, 2007a) and CEF (Moura et al, 2007b) of the bull was already reported. In addition, there is practically no information about the role of nucleobindin in the male reproductive tract, and herein this work brings new information about this protein's interaction with the midpiece of ejaculated sperm, suggesting that the multifunctional nucleobindin may in fact influence sperm metabolism.…”
mentioning
confidence: 79%
“…PGDS has been reported to be more prevalent in the seminal plasma of high fertility bulls (Killian et al, 1993;Gerena et al, 1998). Although there is only one form of PGDS detectable in 2-D gels of bovine seminal plasma, in the cauda epididymal fluid (CEF) PGDS is composed by a series of four spots, which comprise 7.6% of all protein spots quantified in the CEF gels (Moura et al, 2007b). Three of these PGDS isoforms, however, were found to be 2 to 3-fold more abundant in the CEF of low fertility males (Moura et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…seminal plasma from high fertility bulls can act to improve the fertilizing potential of low-fertility bulls (Henault et al 1995). Detailed proteomic studies of accessory gland fluids have shown consistent differences in high-/low-fertility groups, where four interesting proteins were identified: bovine seminal plasma 30 kDa (sperm capacitation), osteopontin (sperm-oolema interaction), phospholipase A2 (acrosome reaction) and spermadhesin Z13 (sperm motility) as contributing to the higher fertility (Moura et al 2006(Moura et al , 2007a(Moura et al , 2007b. Examination of fertility in bulls is a very powerful approach as it allows in vitro studies to be complemented with data in vivo.…”
Section: Calcium Oscillations In Sperm -A New Signalling System?mentioning
confidence: 99%